PROPOSAL METHODOLOGY FOR ANALYSIS OF POPULATION VULNERABILITY AT HAZARD AREAS - Trentin, Romario; Robaina, Luís Eduardo de Souza; Avila, Luciele de Oliveira (Mercator; Vol. 18 (2019), 2019)
This work presents a discussion of the methodology used to establish the vulnerability associated with at-risk areas in Santa Maria city. The following were used in order to analyze vulnerability: urban-constructive variables, which define the Urban Vulnerability Index (InVU), in addition to further socio-economic variables and urban densification, which define the Human Vulnerability Index (InVH). The InVU is determined by the Urban-Construction Standard, identified through the analysis of occupation planning, housing characteristics and the available infrastructure. The InVH was determined by an analysis of Socioeconomic Variables and Densification. The socioeconomic variables used are the age range of the population, monthly income and the literacy rate. Keywords : Vulnerability Index; Risk Situations; Methodology.